SOSIALISASI DAMPAK NEGATIF PENGGUNAAN MEDIA SOSIAL SECARA BERLEBIHAN TERHADAP ANAK - Sutar Oktaviana Tampubolon; Mariani; Deta Sonia Manik (PT. Jurnal Center Indonesia Publisher, 2024)
Social media is an online tool or media used by users to search for the information they need. Apart from that, social media itself can be used as a communication tool. Moreover, nowadays everything humans need can be accessed on social media in a very short time. Social media has gone viral for all groups, including children, teenagers and even adults. The development of social media makes performance faster, more precise and accurate so that it can increase the resulting productivity. The social media that are often used today are Facebook, Twitter, Instagram, Instagram, WhatsApp and other social media. One of the users of social media now is students, because by using social media students can easily communicate near or long distance without having to meet face to face or meet. Social media for students is important not only as a place to obtain interesting information but has also become a lifestyle. Where one student can have more than one social media. Excessive use of social media for students can have a negative impact. One of the negative impacts of using social media is that it makes students lazy, damages their health, rarely talks with friends and so on. Thus, we as the proponents want to provide socialization activities on the positive and negative impacts of excessive use of social media on fifth grade elementary school students. This activity is expected to provide benefits for students and also help the role of teachers in developing students in using social media. Keywords: socialization, social media, negative impact